Effect of Acute Appendicitis on routine Liver Function Tests - Khan, S (Journal of Institute of Medicine Nepal, 2008)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if !mso]> <![endif]--> <!--[if gte mso 10]> <![endif]--> Background: Liver plays a central role in metabolism and host defense mechanism. It is the first organ to receive substances absorbed or microorganism translocated from gastro intestinal tract (GIT). The aim was to evaluate the effect of acute inflammation of appendix on routine liver function test. Method: 50 cases with no history of hepatotoxic drug intake, non -alcoholic or alcoholic with AST (SGOT)/ALT (SGPT) Result: Among 50 cases 49 cases were of acute appendicitis and its complications. Serum bilirubin was raised in 87.7% cases. It was mixed type in majority (84.6%) of the cases. The average level of serum bilirubin was 2.34 mg/dL. Serum Alanine Amino Transferase (ALT) was normal in 73.46% of the cases where as elevated in 26.54% of the case. Aspertate. Age and sex adjusted alkaline phosphatase (ALP) was normal in 51.2% of the cases where as it was elevated in 48.98% of the cases. Amino Transferase (AST) was normal in 61.22% cases whereas elevated in 38.77% of the cases Conclusion: There was mixed type of hyperbilirubinemia and that was due to dysfunction rather than damage of the hepatocyte. This might be due to combined effect of depressed hepatocellular uptake of unconjugated bilirubin and excretion of the conjugated bilirubin by bacteria, their toxins or cytokines. The elevation of AST and ALP is of no diagnostic value where as elevation (?1times) of ALT can be helpful to rule out acute inflammation of appendix at 95% level of confidence in clinically suspected cases of acute appendicitis. Key Words: Acute Inflammation of Appendix, Acute appendicitis, Hyperbilirubinemia, Routine liver function tests. Journal of Institute of Medicine, April, 2008; 30:1 41-45 The full text of this paper is available from the Journal of Institute of Medicine website